Factors Influencing The Incident Of Stunting In West Lancang Village, Dewantara District, North Aceh Regency, 2024 - Rildayani Rildayani; Myrna Lestari AB; Elvieta Elvieta (CV. AFDIFAL MAJU BERKAH, 2026)
Stunting remains a major public health problem that affects child growth and development, particularly in developing countries, including Indonesia. This study aimed to identify factors associated with stunting among children aged 12–23 months in Lancang Barat Village, Dewantara District, North Aceh Regency, in 2024. A quantitative study with a cross-sectional design was conducted involving 75 mothers and their children, selected using total sampling. Data were collected through structured questionnaires and anthropometric measurements. The independent variables included maternal height, maternal education, and exclusive breastfeeding practices, while the dependent variable was the incidence of stunting. Data analysis consisted of univariate and bivariate analyses using the Chi-square test with a significance level of α = 0.05. The results showed that 20.0% of children were stunted or severely stunted. Statistical analysis revealed a significant association between maternal height and stunting (p = 0.002), maternal education and stunting (p = 0.007), and exclusive breastfeeding and stunting (p = 0.001). In conclusion, maternal height, maternal education, and exclusive breastfeeding practices are significant factors influencing stunting among children in Lancang Barat Village. Strengthening maternal education and promoting exclusive breastfeeding are essential strategies to reduce stunting prevalence.